Sterol and triterpenoids from Hygrophila schulli Buch.-Ham. - Suflan, Md Abu; Begum, Fatema; Haque, Mohammad Rashedul; Hasan, Choudhury Mamood; Rashid, Mohammad Abdur (Bangladesh Journal of Botany, 2018)
The methanol extract of whole plants of Hygrophila schulli Buch.-Ham. was subjected to repeated chromatographic separation and purification processes to isolate its chemical constituents. A total of three compounds were isolated which have been characterized as stigmasterol, lupeol and lup-20(29)-ene-3β,23- diol on the basis of 1H NMR spectral evidence and confirmed by comparing with published data, as well as co-TLC in case of stigmasterol and lupeol. This is the first report of lup-20(29)-ene-3β,23-diol from this plant.